2017
DOI: 10.1080/10826084.2017.1349801
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal and Intrapersonal Differences among Adolescent Nonsmokers, Ex-Smokers, and Smokers

Abstract: Results from a discriminant function analysis showed that smokers and ex-smokers reported more disinhibition, impulsivity, number of friends who smoke and less self-control under peer pressure to smoke compared to nonsmokers. Ex-smokers reported less metacognitive processes, more smoking-related risk perception and were less likely to have parents who smoke. Conclusions/Importance: Interventions and campaigns aimed to persuade adolescents to stop smoking should work to develop adaptive metacognitive skills and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…19,24 Other factors affecting an adolescent's decision to smoke include (a) grade level, where the higher the grade a student is, the higher the chances that the student smokes cigarettes 21 , (b) peers, where the more smoker friends an adolescent has, the higher likelihood of smoking, even alcohol use. 25,26 and (c) media, where viewing movie depictions of tobacco use is associated with higher receptivity to smoking. 27 The environment per se is a societal factor, which includes cigarette taxes and prices, as well as implementation of smoking prevention programs specifically for the youth.…”
Section: Risk Factors For Adolescent Smokingmentioning
confidence: 99%
“…19,24 Other factors affecting an adolescent's decision to smoke include (a) grade level, where the higher the grade a student is, the higher the chances that the student smokes cigarettes 21 , (b) peers, where the more smoker friends an adolescent has, the higher likelihood of smoking, even alcohol use. 25,26 and (c) media, where viewing movie depictions of tobacco use is associated with higher receptivity to smoking. 27 The environment per se is a societal factor, which includes cigarette taxes and prices, as well as implementation of smoking prevention programs specifically for the youth.…”
Section: Risk Factors For Adolescent Smokingmentioning
confidence: 99%
“…For example, previous research has found that ex-smokers are more likely to relapse when they contact smokers [ 10 , 11 ]. In addition, researchers also found that social interaction with other smokers is a crucial factor in motivating individuals to initiate, continue, and restart smoking [ 12 , 13 , 14 , 15 ]. Meanwhile, when a group of smokers gathers, smokers usually share cigarettes and persuade each other to smoke, which may cause more social smoking behavior [ 16 ].…”
Section: Introductionmentioning
confidence: 99%